2019
DOI: 10.1017/s1355617719001164
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Executive Functioning in Patients with Meningioma and Low-Grade Glioma: A Comparison of Self-Report, Proxy-Report, and Test Performance

Abstract: Objective:This study aimed to examine: (1) patient–proxy agreement on executive functioning (EF) of patients with primary brain tumors, (2) the relationships between patient- and proxy-report with performance-based measures of EF, and (3) the potential influence of performance-based measures on the level of agreement.Methods:Meningioma and low-grade glioma patients and their informal caregivers completed the Behavior Rating Inventory of Executive Function (BRIEF-A) 3 months after surgery. The two index scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
5
17
1
Order By: Relevance
“…The third hypothesis was confirmed: comparisons between patients' self-reported measures and caregivers' reports showed a high level of concordance between both types of ratings, for all executive domains considered. This result fits well with that of a recent study published by Van der Linden et al [40], which highlights a moderate level of agreement between patients with PBT and their proxies with the BRIEF-A. This study appears complementary to that study, which did not include survivors (on average, patients were recruited three months after surgery).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The third hypothesis was confirmed: comparisons between patients' self-reported measures and caregivers' reports showed a high level of concordance between both types of ratings, for all executive domains considered. This result fits well with that of a recent study published by Van der Linden et al [40], which highlights a moderate level of agreement between patients with PBT and their proxies with the BRIEF-A. This study appears complementary to that study, which did not include survivors (on average, patients were recruited three months after surgery).…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that there are only two very recent studies devoted to this topic in adult PBT patients. One of them examined executive self-assessment exclusively [35], while the other did not include the study of survivors [40]. 1.…”
Section: Introductionmentioning
confidence: 99%
“…This incongruence is observed in both directions: there are patients who report no problems and have impaired test performance, and patients who report language problems and have no impaired test performance. Although remarkable, a similar incongruence has been reported previously in brain tumour patients for language as well as cognitive functioning Gehring et al, 2015;Pranckeviciene et al, 2017;Van der Linden et al, 2020). This implies that a task-related explanation for the observed inconsistency is unlikely.…”
Section: Main Outcomes In Contextsupporting
confidence: 79%
“…Although remarkable, this is in line with previous literature. A low congruence between subjective complaints and objective test results has been reported for language Pranckeviciene et al, 2017), and is a common finding for cognitive functioning in brain tumour patients Pranckeviciene et al, 2017;Van der Linden et al, 2020). In our study, incongruence is observed in both directions: (1) patients report no language problems, but have impaired test performance; (2) patients report language problems, but have no impaired test performance.…”
Section: Language Change After Surgerycontrasting
confidence: 42%
“…As childhood cancer (CC) survival rates have been increasing considerably over the past few decades, special attention has been paid to adverse late effects. Even though cancer treatment protocols are continuously modified to reduce long-term sequelae (Mucci & Torno, 2015), cognitive late effects are often reported (Krull et al, 2018;van der Linden et al, 2020). Cognitive problems likely affect psychosocial behaviour and health-related quality of life (Ehrhardt et al, 2018;Tonning Olsson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%